Penguasaan Keterampilan Dasar Mengajar Mahasiswa Program Studi Pendidikan Bahasa Arab di Universitas Negeri Jakarta - Fatwa Arifah; Chakam Failasuf; Erika Novianisa (Al-Ma‘rifah, 2020)
This study aims to get a clear description of the basic teaching skills for students of the Arabic Language Education Study Program, Faculty of Languages and Arts, Universitas Negeri Jakarta. The research method used in this study is a mixed-method which is a combination of quantitative research methods and qualitative research methods. The research location is in one of the Universitas Negeri Jakarta classrooms and the research subjects consisted of 45 students class of 2016 in the Arabic Language Education Study Program who took Micro Teaching course. Data collection techniques using observation and documentation instruments. The percentage of the highest to lowest average scores in basic teaching skills mastered by students on the exam, small groups and individuals, with a value of 89.42% in the very good category, and skills of reinforcement obtained an average value of 85.00% with enough category. With this research, researchers gain an understanding of basic teaching skills as well as data related to teaching skills in the Arabic Language Education Study Program, Universitas Negeri Jakarta. This research also can be used as a guideline for other researchers regarding basic teaching skills.